2016
DOI: 10.12659/msm.898202
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Omentin-1 Concentrations with the Presence of Atrial Fibrillation

Abstract: BackgroundOmentin-1 is one of the adipokines associated with obesity, diabetes, and coronary heart disease development. We determined to investigate whether serum omentin-1 concentrations were correlated with the presence of atrial fibrillation (AF).Material/MethodsSerum omentin-1 concentrations were examined in a cross-sectional population that included 220 patients with AF (70 with paroxysmal AF, 78 with persistent AF, and 72 with permanent AF) and 115 healthy controls.ResultsReduced serum omentin-1 concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 22 publications
0
20
0
3
Order By: Relevance
“…Serum omentin-1 is one of the adipokines known to be present in obesity, DM, and CAD. Further investigations under the same study showed that patients with permanent AF have even lower concentrations of serum omentin-1 than patients with paroxysmal AF [35].…”
Section: Potential Approaches To Management and Treatmentmentioning
confidence: 78%
“…Serum omentin-1 is one of the adipokines known to be present in obesity, DM, and CAD. Further investigations under the same study showed that patients with permanent AF have even lower concentrations of serum omentin-1 than patients with paroxysmal AF [35].…”
Section: Potential Approaches To Management and Treatmentmentioning
confidence: 78%
“…38,39 It is a known knowledge that hypertension, diabetes, visceral obesity, and smoking are the risk factors increasing the prevalence of AF and this increases with age; however, it is assumed that there is a causal connection between epicardial fat tissue and AF beyond classical cardiovascular risk factors. 14 In studies conducted with nondialysis patient populations, EFT thickness (regardless of age, obesity, hypertension, and diabetes) was found to increase in people with AF [12][13][14][15]. There are no studies that examined the relationship between EFT thickness and AF in dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…В последние годы появились работы, доказывающие позитивную роль оментина в предотвращении ФП [46][47][48][49]. Оментин-1 -белок, который преимущественно секретируется стромально-сосудистыми клетками жировой ткани.…”
unclassified
“…В экспериментальных работах доказано, что оментин-1 обладает антиокислительными и противовоспалительными свойствами. В исследовании [49] у пациентов с ФП концентрация сывороточного оментина-1 была достоверно ниже, чему больных с синусовым ритмом. При этом наиболее низкие значения оментина-1 были обнаружены у пациентов с постоянной формой ФП по сравнению с больными с персистирующей или пароксизмальной формой аритмии.…”
unclassified
See 1 more Smart Citation